Difference of clogging performance between radial and swept back impeller of axial pump. Issue 1 (1st April 2022) - Kondo, Y; Miura, K; Miyagawa, K; Nohmi, M; Tsuneda, T
Abstract: An axial pump which is used to pump water out of a river often sucks in solid bodies such as leaves and branches. These foreign substances may clog the passage and lead to dangerous conditions such as a decline in the performance of the pump. In this investigation, we conducted the clogging experiments by putting polyester strings in an axial drain pump which has two types of impellers, a radial blade impeller and a swept back blade impeller. By visualizing behavior of the strings in the pump using a high-speed video camera, we compared the anti-clogging performance between the two impellers and investigated the mechanism of clogging. The results of these experiments showed that the pass rate of the strings that flowed into the swept back blade impeller was higher than that in the radial blade impeller. It is because strings that are caught in the leading edge of the swept back blade tend to move to the tip side and be pulled towards the suction surface. In addition to the experiments, we carried out the simulations of these experiments using a CFD-DEM (Discrete Element Method) coupling analysis. The results were in good agreement with the experiments qualitatively.